Analisis Prosedur Pemeriksaan Magnetic Resonance Spectroscopy (MRS) Pada Kasus Tumor Otak - Putri Susilowati; Widya Nurmayanti (Poltekkes Kemenkes Semarang, 2020)
Background: Magnetic Resonance Spectroscopy (MRS) is a method for measuring or assessing changes in the chemical elements of brain tissue in abnormalities such as tumours, stroke, epilepsy, metabolic disorder, infections, and neurodegenerative disease. MRS sequences require techniques to suppress fat and water signals, so the value of metabolic elements such as NAA Choline, Creatine, Lipids, and Lactate not been covered by fat and water. The peak amplitude of metabolic elements in MRS depends on the parameter used in the MRS sequences especially TE. Some studies suggest that variation and combinations of TE can provide more complete information on metabolite element, and can even be used to grading tumour stages.Methods: Type of this research is a qualitative study with an observational approach. Data collection was conducted in June 2019 at Radiology Department with observation method, unstructured interview, and documentation related to Magnetic Resonance Spectroscopy procedures. Data processing and analysis are carried out descriptively related to the result of observation, interview, and documentation.Results: The Head MR Spectroscopy examination procedure is a follow-up procedure of contrast MRI of the head. The main metabolite elements assessed on MRS are NAA, Choline, and Creatine, while those calculated and analyzed are the Area Under Cover (AUC) Integrals which are a collection of NAA and Choline signals. MRS sequences use Multi Voxel Spectroscopy (MVS). Chemical Shift Imaging (CSI) is used to suppress fat and water signals. TE parameter used in MRS sequences is only intermediate 135 ms.